The image and status of librarians in the Philippines perceptions by selected library users - Angeles, Chito N.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
This study attempts to determine the perceptions of library users on the profession and practice of librarianship. It seeks to discover the relationship between the image and status of librarians. It also seeks to find out the present status of librarians in relation to other professionals and to determine the differences in their status in relation to the type of library where they are employed.
Subjects of the study include students, teachers, library employees, and other users of library services randomly selected from the four types of libraries in the city of Manila. Two schools/institutions for every type of library were selected to be the respondents of the structured questionnaire. The libraries included are: University of the Philippines Manila, College of Arts and Sciences Library and Philippine Normal University (academic); Pope Pius XII Catholic Center Library and World Health Organization Western Pacific Regional Office Library (special); Department of Justice Legal Library and Department of Tourism Library (public/government); and Santa Isabel College, High School Library and Araullo High School Library (school). A total of 180 questionnaires were distributed among the selected libraries and about 170 or 94.445 were gathered back.
Findings of the study reveal that library users generally perceived librarians to be helpful, approachable, friendly, orderly, and patient while their work was perceived as useful, helpful, challenging and interesting. The image and status of librarians were related to the type of library where they work and that special librarians have the highest status among others. Finally, there is a relationship between the image and status of librarians in the Philippines. This is seen in the case of academic librarians having a poor image and a low status.
Typescript.
Vita
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman